Dupilumab for the treatment of COPD: protocol for a systematic review and meta-analysis - Bingyu Xue; Bingyu Xue; Qionghua Xiao; Qionghua Xiao; Yuanming Huang; Yuanming Huang; Minghang Wang (Frontiers in Medicine)
IntroductionChronic obstructive pulmonary disease (COPD) is a significant global public health issue, with a high incidence and mortality burdening patients heavily. Although existing treatment methods have made certain progress, their effectiveness in intervention during acute exacerbations and long-term management remains suboptimal for some patients. In recent years, biologic agents have provided new directions for COPD treatment. Dupilumab, a humanized monoclonal antibody targeting IL-4Rα, has shown good efficacy in type 2 inflammation-related diseases; however, its efficacy and safety in COPD treatment remain to be verified.Methods and analysisThis study will assess the efficacy and safety of dupilumab in the treatment of COPD through a systematic review and meta-analysis. Randomized controlled trials (RCTs) meeting the inclusion criteria will be included, and the Population-Intervention-Comparator-Outcome-Study (PICOS) research design standard will be adopted to compare the efficacy of dupilumab against placebo or conventional treatment. The primary outcome will be the annual exacerbation rate (AER) of COPD, and the secondary outcomes will include changes in FEV1 before baseline bronchodilators, St. George’s Respiratory Questionnaire (SGRQ) scores, Evaluating Respiratory Symptoms in COPD (E-RS COPD) and blood eosinophil counts. Safety will also be assessed, and the incidence of adverse reactions will be statistically analyzed. A literature search will be conducted across multiple databases, including PubMed, Embase, WOS, Cochrane Library, and Scopus. Ultimately, this study will assess the impact of dupilumab on COPD patients through meta-analysis, aiming to provide new evidence-based insights for the treatment of COPD.Ethics and disseminationEthical approval is not required for this review. Upon completion, the results of this review will be submitted to peer-reviewed journals for publication and/or presented at academic conferences.Trial registration numberhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024605417.